Cities and Spaces of Leadership - D'Alessandro, Cristina. author. aut Link
XII, 208 p.
Keywords: Cristina D'Alessandro and Frannie Léautier investigate the interaction between leaders and the various spaces and places in which they work and live. Rooting their work in a critical understanding of the global contemporary world, they combine human geography and leadership theories throughout the book. Referring to the trajectories of global leaders, Cities and Spaces of Leadership is a unique and unprecedented achievement that should be read by geographers, leaders, and academics concerned by contemporary social, political and economic dynamics.